PENGARUH OPINI AUDIT DAN TINGKAT PERTUMBUHAN PERUSAHAAN TERHADAP PERGANTIAN AUDITOR - NURYANTI, LELY (Jurnal Akuntansi AKUNESA, 2012)
The purpose of this study is to analyze the effect of audit opinion and the growth rate of manufacturing companies listed in the Indonesia Stock Exchange to auditor switch after the enactment of mandatory regulations in 2008. Hypothesis testing technique in this study used logistic regression models. The selection of the sample used purposive sampling method and selected based on established criteria. Companies sampled in this study consists of twelve companies over the period 2008-2011. The results of this study indicate that the audit opinion and company growth rate does not affect the auditor switch. Keywords: audit opinion, the rate of growth, auditor switch